2022
DOI: 10.2217/nnm-2022-0124
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Molecular Imaging in the Second Near-Infrared Window

Abstract: Near-infrared-II (NIR-II) fluorescence imaging has rapidly developed for the noninvasive investigation of physiological and pathological activities in living organisms with high spatiotemporal resolution. However, the penetration depth of fluorescence restricts its ability to provide deep anatomical information. Scientists integrate NIR-II fluorescence imaging with other imaging modes (such as photoacoustic and magnetic resonance imaging) to create multimodal imaging that can acquire detailed anatomical and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Additionally, some studies suggested that green uorescent protein-transfected cells could emit green uorescence with the assistance of the in vivo imaging systems, although most studies of green uorescent protein-labeled cells after transplantation have so far been limited to tissue sections [15]. Since 2019, the exploration of the second near-infrared window (NIR-II; 1,000-1,700 nm) optical imaging system, and the development and utilization of new uorescent probes have driven advances in real-time visualization and monitoring of post-transplant stem cells in vivo [16,17]. NIR-II optical imaging system can detect tissue at depths of centimeters and achieve micron resolution at millimeter depths.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies suggested that green uorescent protein-transfected cells could emit green uorescence with the assistance of the in vivo imaging systems, although most studies of green uorescent protein-labeled cells after transplantation have so far been limited to tissue sections [15]. Since 2019, the exploration of the second near-infrared window (NIR-II; 1,000-1,700 nm) optical imaging system, and the development and utilization of new uorescent probes have driven advances in real-time visualization and monitoring of post-transplant stem cells in vivo [16,17]. NIR-II optical imaging system can detect tissue at depths of centimeters and achieve micron resolution at millimeter depths.…”
Section: Introductionmentioning
confidence: 99%